An Ethylene-inhibited NF-YC Transcription Factor RhNF-YC9 Regulates Petal Expansion in Rose - Changxi Chen; Nisar Hussain; Yaru Wang; Mingtong Li; Lin Liu; Meizhu Qin; Nan Ma; Junping Gao; Xiaoming Sun (Horticultural Plant Journal, 2020)
The speed of flower opening is closely related to their ornamental period. Ethylene functions as a negative regulator involved in the regulation of the petal expansion process. In this study, we isolated a NF-YC transcription factor gene, RhNF-YC9, from rose petals. RhNF-YC9 expression was induced at the early stages of flower opening but was inhibited by ethylene treatment. Silencing RhNF-YC9 decreased the speed of petal expansion from stage 2 to stage 5. The expressions of 11 cell expansion-related genes involved in cell wall loosening, cell turgor modulation, and cytoskeleton remodeling were significantly down-regulated in RhNF-YC9-silenced petals. We also found that silencing RhNF-YC9 decreased the expression of gibberellin acid (GA) biosynthetic gene RhGA20ox while significantly increasing the transcripts of GA catabolic gene RhGA2ox, reducing the accumulation of GA4 and GA7. The influence of ethylene treatment on the expression of RhGA20ox and RhGA2ox showed the same trend. These results together suggested that RhNF-YC9 positively regulated the speed of petal expansion and mediated the crosstalk between ethylene and GA. Our findings revealed a new insight into the function of NF-YC transcription factors involved in ethylene-regulated petal expansion.